The position and status of lesbian, gay, bisexual and transgender(LGBT): A legal & moral human rights analysis / Suria Fadhillah Md Pauzi ...[et al.] - Md Pauzi, Suria Fadhillah; Ahmad Jamal, Farah Haneem; Syed Hamid, Sharifah Shatrah; lbrahim, Mohd Syahril (2013)
Sexuality is treated as a sensitive topic and intensely private activity in our culture, hence the discussion on LGBT's issues seem inappropriate especially to our traditional society. However this group faces extreme forms of prejudice in marry areas of life and struggle for the most basic civil rights such as fundamental right of access to employment or to have families. At international level, in 2008 94 member-states have rendered their support by signing LGBT Rights Declaration in the United Nation General Assembly whereas 54 member-states have signed a statement opposing the group rights. In 2011 the United Nation Human Rights Council has passed another resolution supporting LGBT rights after initiation made by South Africa. This paper will analyze the legal position and status of LGBT in our country with reference to relevant international conventions, Federal Constitution as our supreme law, Penal Code and selected Shariah State Enactments pertaining to this matter. This paper concludes that it is a legal obligation to safeguard the human rights of LGBT and thus they are entitled to enjoy the protection accorded by international and national law but paramount consideration should be placed on religious, moral and cultural values in supporting their rights by way of legislation.